2021
DOI: 10.3390/cancers13081895
|View full text |Cite
|
Sign up to set email alerts
|

Current Intraoperative Imaging Techniques to Improve Surgical Resection of Laryngeal Cancer: A Systematic Review

Abstract: Laryngeal cancer is a prevalent head and neck malignancy, with poor prognosis and low survival rates for patients with advanced disease. Treatment consists of unimodal therapy through surgery or radiotherapy in early staged tumors, while advanced stage tumors are generally treated with multimodal chemoradiotherapy or (total) laryngectomy followed by radiotherapy. Still, the recurrence rate for advanced laryngeal cancer is between 25 and 50%. In order to improve surgical resection of laryngeal cancer and reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 72 publications
0
13
0
Order By: Relevance
“…In this section attention is paid prevalently to the biomolecules acting as endogenous fluorophores and to their possible pathophysiological meaning, rather than on the almost countless clinical optically based diagnostic applications described in dedicated papers and reviews [264][265][266][267][268][269][270][271][272][273].…”
Section: Normal and Altered Cell And Tissuesmentioning
confidence: 99%
“…In this section attention is paid prevalently to the biomolecules acting as endogenous fluorophores and to their possible pathophysiological meaning, rather than on the almost countless clinical optically based diagnostic applications described in dedicated papers and reviews [264][265][266][267][268][269][270][271][272][273].…”
Section: Normal and Altered Cell And Tissuesmentioning
confidence: 99%
“…Although progress has been made in the comprehensive management of patients with LSCC, the 5‐year overall survival (OS) rate had reduced over the past 50 years, owing to the insidious symptoms and lack of effective diagnostic methods for early stages. 2 Approximately 60% of the patients with LSCC are diagnosed at an advanced stage or even with metastasis of the lymph node, and have had a poor prognosis. 3 Recently, more and more evidence has demonstrated that the prognosis and chemotherapeutic efficacy of patients with tumor was largely affected by the infiltration of the immune cells.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, due to the strong absorption of blue light by the optical characteristics of hemoglobin, NBI can also clearly display the submucosal microvascular morphology. The image provided by optical enhancement technology emphasizes the morphology and surface structure of mucosal blood vessels and enhances the visibility of blood vessels and other structures on the mucosal surface, which is conducive to the detection of lesions and enables it to obtain a visual effect similar to that of chemical staining under endoscopy [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%